2009
DOI: 10.1063/1.3072075
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear-dynamical-system approach to microwave-assisted magnetization dynamics (invited)

Abstract: Methods of nonlinear-dynamical-system theory are applied to the study of magnetization dynamics under the action of microwave magnetic fields. In the case of a system with uniaxial anisotropy subject to a circularly-polarized microwave field, the conditions are derived under which the magnetization reversal field is substantially reduced by the application of the microwave field. The dependence of magnetization switching on microwave-field-pulse duration is discussed and analytical expressions are derived for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 30 publications
7
47
0
Order By: Relevance
“…As theoretically proposed by Bertotti et al, the magnetization dynamics under the action of a rf magnetic field can be identified as static switching of the magnetization by adopting a rotating reference frame in which the rf field is stationary. 20,21 In the rotating frame, an effective magnetic field proportional to the frequency of the rf field is generated along the easy axis of magnetization and facilitates magnetization reversal.…”
Section: Introductionmentioning
confidence: 99%
“…As theoretically proposed by Bertotti et al, the magnetization dynamics under the action of a rf magnetic field can be identified as static switching of the magnetization by adopting a rotating reference frame in which the rf field is stationary. 20,21 In the rotating frame, an effective magnetic field proportional to the frequency of the rf field is generated along the easy axis of magnetization and facilitates magnetization reversal.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, this is because the rotating field plays a key role in the microwave-assisted switching [17][18][19][20][21][22] and, on the other hand, because the corresponding dynamical equations (without accounting the thermal fluctuations) can often be solved analytically. [23][24][25][26][27] Specifically, it has been shown 23 (see also Ref. 28) that the rotating field can induce two types of the stable precessional modes of the magnetic moment, namely, the periodic (P) and quasiperiodic (Q) modes.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is currently attracting much attention, and the mechanisms implied in the magnetization dynamics during the switching (coherent rotation, vortex core switching, domain wall propagation, etc.) are still open questions, as shown by the important number of experimental [1][2][3][4] and simulation studies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%